2004
DOI: 10.1042/bj20031567
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of DNA methylation patterns in transgenic Drosophila overexpressing mouse DNA methyltransferases

Abstract: DNA methyltransferases (Dnmts) mediate the epigenetic modification of eukaryotic genomes. Mammalian DNA methylation patterns are established and maintained by co-operative interactions among the Dnmt proteins Dnmt1, Dnmt3a and Dnmt3b. Owing to their simultaneous presence in mammalian cells, the activities of individual Dnmt have not yet been determined. This includes a fourth putative Dnmt, namely Dnmt2, which has failed to reveal any activity in previous assays. We have now established transgenic Drosophila s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…Both of these effects are consistent with the known preferences of the DNMT3a methylase for certain flanking sequences in CpGs (see SI Fig. 7) (26) and its ability to methylate cytosines in non-CpG dinucleotides, albeit much less effectively (27)(28)(29). Additionally, the overall relative proportions of methylation found in the dinucleotides CpG, CpA, CpT, and CpC correlate well with the known propensities of the DNMT3a methylase for these sites.…”
Section: Sequence-specific In Vivo Methylation Of Mtdna By a Chimericsupporting
confidence: 71%
“…Both of these effects are consistent with the known preferences of the DNMT3a methylase for certain flanking sequences in CpGs (see SI Fig. 7) (26) and its ability to methylate cytosines in non-CpG dinucleotides, albeit much less effectively (27)(28)(29). Additionally, the overall relative proportions of methylation found in the dinucleotides CpG, CpA, CpT, and CpC correlate well with the known propensities of the DNMT3a methylase for these sites.…”
Section: Sequence-specific In Vivo Methylation Of Mtdna By a Chimericsupporting
confidence: 71%
“…However, the biggest question about Dnmt2 is related to its enzymatic function. In recent years, a number of reports have emerged purporting to demonstrate that Dnmt2 methylates DNA (Pinarbasi et al 1996;Hermann et al 2003;Kunert et al 2003;Liu et al 2003;Narsa Reddy et al 2003;Tang et al 2003;Fisher et al 2004;Mund et al 2004;Kuhlmann et al 2005;Ferres-Marco et al 2006;Katoh et al 2006) or that it does not methylate DNA (Okano et al 1998;Van Den Wyngaert et al 1998;Yoder and Bestor 1998;Dong et al 2001, Goll et al 2006). Yet, more recently it has been shown that Dnmt2 methylates RNA, not DNA, in vitro (Goll et al 2006, Rai et al 2007) and has an in vivo role in zebrafish that is more consistent with RNA methylation than DNA methylation (Rai et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…137,138 Only non-CpG methylations, like CpC, CpT and TpC, are relevant to pyrimidine-motif triplexes. Such modifications have been reported in plants, 139 flies 140 and mammals 141,142 and seem to be mediated by the protein Dnmt2, 140,142 and Dnmt3b. 143 Dnmt2 appears in fact to be an RNA methyltransferase 144,145 that plays an important role in developmental processes 146 while Dmnt3b has been associated with hypermethylation of non-CpG cytosines at the PCG-1alpha promoter in human diabetic patients 143 and has recently been suggested to associate with TFO-induced triplexes.…”
Section: Regulation Of the Regulator?mentioning
confidence: 99%